Inhibitory Molecules That Regulate Expansion and Restoration of HCV-Specific CD4 + T Cells in Patients With Chronic Infection - Raziorrouh, Bijan; Ulsenheimer, Axel; Schraut, Winfried; Heeg, Malte; Kurktschiev, Peter; Zachoval, Reinhart; Jung, Maria–Christina; Thimme, Robert; Neumann–Haefelin, Christoph; Horster, Sophia; Wächtler, Martin; Spannagl, Michael; et al. (Gastroenterology (New York, N.Y. 1943), 2011)
Inhibitory receptors such as programmed death 1 (PD-1) and cytotoxic T lymphocyte–associated antigen (CTLA)-4 mediate CD8 + T-cell exhaustion during chronic viral infection, but little is known about roles in dysfunction of CD4 + T cells. We investigated the functions of inhibitory molecules on hepatitis C virus (HCV)-, influenza-, and Epstein–Barr virus (EBV)-specific CD4 + T cells in patients with chronic infections compared with patients with resolved HCV infection and healthy donors. Expression of PD-1, CTLA-4, CD305, and CD200R were analyzed on HCV-specific CD4 + T cells, isolated from peripheral blood using major histocompatibility complex class II tetramers. We investigated the effects of in vitro inhibition of various inhibitory pathways on proliferation and cytokine production by CD4 + T cells, and we compared these effects with those from inhibition of interleukin (IL)-10 and transforming growth factor (TGF)-β1. PD-1 and CTLA-4 were up-regulated on virus-specific CD4 + T cells from patients with chronic HCV infections. PD-1 expression was lower on influenza- than on HCV-specific CD4 + T cells from subjects with chronic HCV infection, whereas CTLA-4 was expressed at similar levels, independent of their specificity. CD305 and CD200R were up-regulated in HCV resolvers. Blockade of PD-L1/2, IL-10, and TGF-β1 increased expansion of CD4 + T cells in patients with chronic HCV, whereas inhibition of IL-10 and TGF-β1 was most effective in restoring HCV-specific production of interferon gamma, IL-2, and tumor necrosis factor α. We characterized expression of inhibitory molecules on HCV-, influenza-, and EBV-specific CD4 + T cells and the effects of in vitro blockade on CD4 + T-cell expansion and cytokine production. Inhibition of PD-1, IL-10, and TGF-β1 is most efficient in restoration of HCV-specific CD4 + T cells.